Number of Breast Milk Bacteria in Women with Normal Labor and Caesarean Delivery During Room Temperature Storage - Habibah, Siti Noor; Muhlisin, Ahmad; Lutpiatina, Leka; Insana, Aima (Tropical Health and Medical Research, 2024)
The presence of microbes in each breast milk sample can be different, one of which is influenced by the method of delivery. The research aimed to analyze the effect of storage time for breast milk from mothers giving birth normally and giving birth by Caesarean on the number of bacteria at room temperature. The independent variable in this study was the storage time for breast milk from mothers giving birth normally and giving birth by Caesarean for 0, 4, 8, and 12 hours at room temperature, while the dependent variable in this study was the number of bacteria in the breast milk. The research samples were breast milk from mothers who gave birth normally and Caesarean section which was treated with storage at room temperature for 0, 4, 8, and 12 hours. The results of the research were that the average number of bacteria in breast milk from mothers giving birth normally, stored at 0, 4, 6, 8, and 12 hours respectively, was 1.33 x 104 CFU/ml; 2.18 x 104 CFU/ml; 5.04 x 106 CFU/ml; 1.68 x 107 CFU/ml. The average number of bacteria in breast milk from mothers giving birth by Caesarean storage 0, 4, 6, 8, and 12 hours respectively 1.83 x 104 CFU/ml; 1.73 x 105 CFU/ml; 1.76 x 107 CFU/ml; 6.67 x 107 CFU/ml. There is a significant difference in the number of bacteria between breast milk from mothers who gave birth normally and breast milk from mothers who gave birth by Caesarean section. Storage time has a positive effect on the number of bacteria in breast milk from mothers giving birth normally and giving birth by Caesarean. It is recommended to store breast milk at room temperature for up to 4 hours for breast milk from women giving birth normally and for breast milk from mothers giving birth by Caesarean, storage for less than 4 hours by paying attention to the cleanliness of the breast milk storage area.